Fatal pulmonary thromboembolism - Yakar, A.; Yakar, F.; Ziyade, N.; Yildiz, M.; Uzun, I. (My University, 2016)
OBJECTIVE: Venous thromboembolism is a complex, multifactorial disease, involving interactions between acquired or inherited predispositions to thrombosis and various risk factors, such as trauma and surgery. This study investigated the clinical features and most important risk factors of fatal pulmonary thromboembolism (PTE).